Authorial presence in academic book reviews: a Thai-English comparison - Klaibanmai, Kamontip (Penerbit Universiti Kebangsaan Malaysia, 2023)
Authorial presence indicates the existence of authors in a text. It also suggests the authoritativeness of writers as they demonstrate their opinions. Closely similar terms are authorial voice or authorial identity and others. This paper defines the concept of authorial presence in relation to one of the marginalised disciplinary discourse – an academic book review. The author in the text here is, therefore, the reviewer. Based on a bilingual multidisciplinary corpus of contemporary academic book reviews in five fields of study, a qualitative text analysis with the use of computerassisted qualitative data analysis software is carried out to elucidate exponents of authorial presence in the texts and to compare the Thai and English reviews in different disciplines. The findings reveal various exponents of authorial presence, which are categorised into overt and covert entities with various sub-categories, e.g. the first-person point of view, the third-person point of view, self-citation, inclusive we, pro-dropping, and the review. Quantified data also indicate striking differences concerning not only linguistic and/or cultural issues but also disciplinary ones. It is expected that this study can contribute to the understanding of authorial presence, which is significant for readers’ comprehension of the text, including the position of the author that is portrayed in it.